RETRACTED: Development of moral and psychological stability of youth through the use of music in the process of teaching spiritual and moral disciplines - Enina Olga (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001